Cannabinoids for the Treatment of Pain: An Update on Recent Clinical Trials. (2005) - Ware, Mark; Beaulieu, Pierre
Abstract : Over the past five years, there has been a considerable increase in clinical research on cannabinoid use for a range of pain syndromes. Cannabinoid products are becoming available for research and clinical use, and pharmaceutical industry interest in the potential for cannabinoids in therapeutics is also gaining momentum. The present article summarizes recent clinical trial data in the field of pain management and suggests that the potential for cannabinoid therapy for chronic pain states is encouraging. Clinicians working in pain management should be aware of the options becoming available from the cannabinoid class of medications.